2011
DOI: 10.1016/j.bbapap.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Design of Factor XIII V34X activation peptides to control ability to interact with thrombin mutants

Abstract: Thrombin helps to activate Factor XIII (FXIII) by hydrolyzing the R37-G38 peptide bond. The resultant transglutaminase introduces cross-links into the fibrin clot. With the development of therapeutic coagulation factors, there is a need to better understand interactions involving FXIII. Such knowledge will help predict ability to activate FXIII and thus ability to promote/hinder the generation of transglutaminase activity. Kinetic parameters have been determined for a series of thrombin species hydrolyzing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 61 publications
(114 reference statements)
1
23
0
Order By: Relevance
“…NMR studies indicated that L34 and P36 promote stabilizing P 4 to P 2 interactions that better anchor the AP segment onto the thrombin active site surface and promote hydrolysis [37]. Additional kinetic studies further demonstrated the critical role that the 34 (P 4 ) position can play in controlling thrombin-catalyzed hydrolysis of the FXIII (28–41) AP segment [25, 3840]. Results with recombinant full length FXIII variants involving these same AP residues support this proposal [41, 42].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…NMR studies indicated that L34 and P36 promote stabilizing P 4 to P 2 interactions that better anchor the AP segment onto the thrombin active site surface and promote hydrolysis [37]. Additional kinetic studies further demonstrated the critical role that the 34 (P 4 ) position can play in controlling thrombin-catalyzed hydrolysis of the FXIII (28–41) AP segment [25, 3840]. Results with recombinant full length FXIII variants involving these same AP residues support this proposal [41, 42].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, FXIIIa catalyzed crosslinking could be initiated earlier or later in the fibrin clot assembly process. Moreover, specific FXIII mutants could be matched with thrombin species that have either procoagulant or anticoagulant properties [3, 4, 19, 40]. To design such FXIII variants, more information is needed on how the FXIII AP segment interacts with specific regions of wild-type thrombin and its potential therapeutic mutants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations